HAKIKAT INTERPRETASI MUHAMMAD SYAHRUR TENTANG POLIGAMI DAN RELEVANSINYA DENGAN HUKUM PERKAWINAN NASIONAL - Andawati Andawati (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2020)
AbstractThis reseach discusses "The essence of the interpretation of Muhammad Syahrūr about Polygamy and its relevance to the National Marriage law”. This study aims to determine the concept of polygamy according to Mohammed Syahrūr, methods Muhammad Syahrūr in understanding the verses on polygamy dan relevansi concept of polygamy Muhammad Syahrūr with nasioanl marriage law. The results of the research in this study; concept of polygamy according to Muhammad Syahrūr polygamy is allowed up to four, with a wife kententuan second, third and kempat must widow with orphans. Muhammad method Syahrūr in understanding the verses on polygamy is a linguistic methods to the theoretical limit (Hudū and limit), as well as the determination of the essential nature in al-Kitab absolute must understand that Hanifiyāh and Istiqamāh. The relevance of the concept of polygamy Muhammad Syahrūr with the National Legal marital law lies in the level of skill and principle, meaning that the principle of monogamy is equally open for skill based with strict terms and conditions.